KETERKAITAN ANTARA PSAK NO. 22 KOMBINASI BISNIS TERHADAP PENYUSUNAN LAPORAN KEUANGAN KONSOLIDASIAN - Okta Azalia, Aileen (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Today in the business world, many companies look like a single company, but in fact the company consists of many separate companies that merge. Business combinations can occur when companies merge which will result in a unified company. Based on PSAK No. 22 regulates how to treat accounting activities business combination (bussinees combination) either acquisition or consolidation of ownership based on the acquisition of net assets and shares. There are conditions and treatments that need to be done by companies that do business combinations. Where after doing a business combination, then the parent company needs to make consolidated financial statements. Consolidation begins on the effective control date. The consolidated financial statements are made because there are controls that do not unify the processes of the companies that carry out the merger. The consolidated financial statements are a requirement provided by the statement of Financial Accounting Standards (PSAK) to provide information on the financial position and results of operations for the parent company and subsidiaries as if the entity were a single entity of the company. This article describes the relationship between PSAK No. 22 regarding business combinations in the preparation of the consolidated financial statements. Keywords: PSAK No. 22, Business Combination, Consolidated Financial Statements.